Brain Cytochrome P450 Aromatase Gene Isoforms and Activity Levels in Atlantic Salmon After Waterborne Exposure to Nominal Environmental Concentrations of the Pharmaceutical Ethynylestradiol and Antifoulant Tributyltin - Lyssimachou, Angeliki; Jenssen, Bjørn Munro; Arukwe, Augustine (Toxicological Sciences, 2006)
In this study, the effects of two environmental endocrine disruptors, the synthetic pharmaceutical estrogen (ethynylestradiol, EE2) and antifoulant (tributyltin, TBT) representing two different modes of action on the endocrine system, were studied on brain steroidogenic pathway of juvenile Atlantic salmon ( Salmo salar ). Neurosteroidogenesis was studied using brain aromatase gene isoforms and enzyme activity, in parallel with typical xenoestrogen responses, such as brain estrogen receptor (ERα) and plasma vitellogenin (Vtg) levels. Fish were exposed to nominal waterborne EE2 (5 and 50 ng/l) and TBT (50 and 250 ng/l) concentrations dissolved in dimethyl sulfoxide (DMSO), singly and in combination. Gene expressions were quantified using real-time PCR with gene-specific primers, aromatase activity was analyzed using the tritiated water-release assay, and plasma Vtg was analyzed using competitive ELISA. Our data show that EE2 induced a concentration-specific modulation of P450aromA, P450aromB, and aromatase activity in addition to ERα and plasma Vtg levels in juvenile salmon at day 3 postexposure. TBT exposure caused both the elevation and inhibition of P450aromA, P450aromB, and aromatase activity levels, depending on concentration, at day 7 postexposure. TBT elevated and inhibited ERα and plasma Vtg and also antagonized EE2-induced expression of the studied variables at day 7 postexposure. Interestingly, the carrier vehicle DMSO modulated the receptor-mediated and non–receptor-mediated estrogenic responses at day 7 postexposure, compared to day 3. In general, these findings suggest that the exposed animals are experiencing impaired steroidogenesis and modulations of receptor-mediated endocrine responses. Given the integral role of neurosteroids in homeostatic process, growth, metabolism, reproduction, and development of central nervous system and function, these effects may have serious impact on this endocrine pathway and potentially affect organismal reproductive performance and health. In conclusion, the ...